2018
DOI: 10.1186/s12885-018-5075-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in long-term survivors of colorectal cancer and its association with all-cause mortality: a German cohort study

Abstract: BackgroundThe group of colorectal cancer (CRC) survivors continues to grow worldwide. Understanding health-related quality of life (HRQOL) determinants and consequences of HRQOL impairments in long-term CRC survivors may help to individualize survivorship care plans. We aimed to i) examine the HRQOL status of CRC long-term survivors, ii) identify cross-sectional sociodemographic and clinical correlates of HRQOL, and iii) investigate the prospective association of HRQOL after CRC diagnosis with all-cause mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 68 publications
9
87
2
Order By: Relevance
“…We also found that MAI score was associated with lower all-cause mortality in participants without cancer, but not in cancer patients. In fact, many studies showed the bene cial effect of mental activity or social activity on the quality of life which was reported to decreased the risk of breast cancer mortality and recurrence 55 , enhanced the colorectal cancer overall survival 56 , and in uenced the cancer patient outcomes, including physical burden, psychosocial burden, and nancial burden 57 . Hence, we believe that whether from improving the mental health of cancer patients or improving the survival rate of non-cancer patients, mental activity should be concerned in older people health.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that MAI score was associated with lower all-cause mortality in participants without cancer, but not in cancer patients. In fact, many studies showed the bene cial effect of mental activity or social activity on the quality of life which was reported to decreased the risk of breast cancer mortality and recurrence 55 , enhanced the colorectal cancer overall survival 56 , and in uenced the cancer patient outcomes, including physical burden, psychosocial burden, and nancial burden 57 . Hence, we believe that whether from improving the mental health of cancer patients or improving the survival rate of non-cancer patients, mental activity should be concerned in older people health.…”
Section: Discussionmentioning
confidence: 99%
“…QoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), which was originally proposed by Aaronson et al 10 The QLQ-C30 includes 30 items and measures 5 functional scales (i.e., physical, role, emotional, cognitive, and social functioning), global health status, financial difficulties, and 8 symptom scales (i.e., fatigue, nausea and vomiting, pain, dyspnea, insomnia, appetite loss, constipation, and diarrhea). 11 A summary score was calculated from 13 scales (excluding global QoL and financial difficulties), with the symptom scales being reversed (100-symptom scale) to obtain a uniform direction of all scales, 12,13…”
Section: Evaluation Tools Of Qolmentioning
confidence: 99%
“…The final model tested consisted of 13 dimensions, 12 which resulted in an initial estimate of 260 individuals. However, we added a loss rate of 20%, thereby increasing the minimum sample size to 286 individuals.…”
Section: Sample Sizementioning
confidence: 99%
“…2 In addition to advancements in cancer treatments, effective patient-provider communication is a major facilitator for optimizing survivorship outcomes. [3][4][5] Communication including, but not limited to, a treatment summary, information on the possible late-term effects of treatment, recommended follow-up screenings to monitor recurrent cancers, and a communication plan between health care providers show promise of improving a patient's understanding of their survivorship care and the potential to improve patientreported survivorship outcomes. 4,5 Consequentially, a poor understanding of the utility of posttreatment survivorship care can be a barrier to adequate survivorship care, as patients may delay the initiation of or reduce adherence to follow-up care screening for recurrent cancers, lack knowledge of the long-term effects of treatment, and have unaddressed psychosocial (ie, emotional and social) supportive care needs.…”
mentioning
confidence: 99%
“…[3][4][5] Communication including, but not limited to, a treatment summary, information on the possible late-term effects of treatment, recommended follow-up screenings to monitor recurrent cancers, and a communication plan between health care providers show promise of improving a patient's understanding of their survivorship care and the potential to improve patientreported survivorship outcomes. 4,5 Consequentially, a poor understanding of the utility of posttreatment survivorship care can be a barrier to adequate survivorship care, as patients may delay the initiation of or reduce adherence to follow-up care screening for recurrent cancers, lack knowledge of the long-term effects of treatment, and have unaddressed psychosocial (ie, emotional and social) supportive care needs. [6][7][8][9] Across health care systems and cancer types, posttreatment patient-provider communication is not standardized, and such heterogeneity in communication can increase survivorship risks associated with poor management of posttreatment care.…”
mentioning
confidence: 99%